A simplified prediction method on Chaboche isotropic/kinematic hardening model parameters of structural steels. (1st June 2023) - Hai, Letian; Wang, Yuanzuo; Ban, Huiyong; Li, Guoqiang; Du, Xiuli
Abstract: The Chaboche combined isotropic/kinematic hardening model has gained wide popularity due to its outstanding description on cyclic stress-strain relations of different structural metals. However, the calibration on material parameters of Chaboche model needs to perform at least a cyclic loading test to gain the experimental data, leading to a considerable time and economic cost. To reduce such calibration expense, a simplified calibration approach was proposed in this paper. Firstly, the Chaboche model parameters of various structural steels, including low yield point steels, mild steels, and high strength steels, were calibrated based upon 171 experimental stress-strain curves by using an identical calibration procedure. Secondly, these parameters calibrated were correlated with the monotonic yield strength and fitted through suitable description formulations. Subsequently, a four-steps prediction method of Chaboche model parameters was proposed to replace the traditional complex calibration approach. Based upon the new prediction method, the values of all Chaboche model parameters can be directly obtained when monotonic yield strength is known. Furthermore, the simulation performance of this new prediction method was validated by comparing a series of simulation stress-strain relations with their experimental counterparts. The probabilistic distribution types of these parameters were accordingly identified and the corresponding statistical parameters were fitted. This study provides a simplified prediction method and a probabilistic description on different Chaboche model parameters, producing a foundation for random analysis of stress-strain behaviors on various structural steels. Highlights: Chaboche model parameters of various structural steels are identified. Relationship between Chaboche model parameters and monotonic properties is studied. A simplified cyclic-test-independent prediction method is established. The applicability of Chaboche model and proposed prediction method are discussed.